2017 IEEE 28th International Symposium on Software Reliability Engineering (ISSRE) 2017
DOI: 10.1109/issre.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Models of Reliability of Fault-Tolerant Software Under Cyber-Attacks

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract -This paper offers a new approach to modelling the effect of cyber-attacks on reliability of software used in industrial control applications. The model is based on the view that successful cyber-attacks introduce failure regions, which are not present in non-compromised software. The model is then extended to cover a fault tolerant architecture, such as the 1-out-of-2 software, popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One of the most challenging parts of the work on applying diversity in practice is the justification of the effectiveness of proposed solutions due to the lack of empirical data. The use of software diversity for security and intrusion-tolerance was proposed in earlier studies reported in [19,20,21,22], which clearly showed the needs for demonstrating the applicability of the proposed architectural solutions and for evaluating their advantages to drive their design.…”
Section: From Analysing Operating System Vulnerabilities To Designingmentioning
confidence: 98%
“…One of the most challenging parts of the work on applying diversity in practice is the justification of the effectiveness of proposed solutions due to the lack of empirical data. The use of software diversity for security and intrusion-tolerance was proposed in earlier studies reported in [19,20,21,22], which clearly showed the needs for demonstrating the applicability of the proposed architectural solutions and for evaluating their advantages to drive their design.…”
Section: From Analysing Operating System Vulnerabilities To Designingmentioning
confidence: 98%
“…The reliability analysis is additional to the existing State Based Quantitative Dependability Analysis. It exploits Mobius's powerful and well-supported analysis capabilities as an engine for safety and security co-engineering, according to the scenario addressed in [117]. Editing Mobius models can be nontrivial, CHESS modeling language fully supports the modeling of system architectures taking into consideration safety and security co-engineering for reliability analysis with MOBIUS.…”
Section: Quantitative Reliability Analysismentioning
confidence: 99%
“…A system is fault-tolerant, if it can provide normal services, even facing the failures of one or more components. [16][17][18] Fault tolerance reduces the risk induced by random errors. Generally, a fault-tolerance system has the following basic characteristics: (1) all single points cannot fail simultaneously; (2) it must be equipped with mechanisms to isolate the failure components and prevent the spread of failure.…”
Section: Physical Securitymentioning
confidence: 99%